2019
DOI: 10.1101/844357
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust banded protoxylem pattern formation through microtubule-based directional ROP diffusion restriction

Abstract: In plant vascular tissue development, different cell wall patterns are formed, offering different mechanical properties optimised for different growth stages. Critical in these patterning processes are Rho of Plants (ROP) proteins, a class of evolutionarily conserved small GTPase proteins responsible for local membrane domain formation in many organisms. While the spotted metaxylem pattern can easily be understood as a result of a Turing-style reaction-diffusion mechanism, it remains an open question how the c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…A Turing-like reaction-diffusion mechanism (Turing 1952) is suggested to initiate patterning of ROP11 in meta-xylem formation, in which ROPGEF4 and ROPGAP3 may act as activator and inhibitor, respectively (Oda and Fukuda 2012b). Alternatively, the difference in diffusion constants between active and inactive ROP11 may drive the Turing mechanism (Jacobs et al 2019). Both mechanisms would explain how ROP11-induced microtubule-free regions are established to spatially control cell wall deposition (Oda and Fukuda 2012a; Oda and Fukuda 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Turing-like reaction-diffusion mechanism (Turing 1952) is suggested to initiate patterning of ROP11 in meta-xylem formation, in which ROPGEF4 and ROPGAP3 may act as activator and inhibitor, respectively (Oda and Fukuda 2012b). Alternatively, the difference in diffusion constants between active and inactive ROP11 may drive the Turing mechanism (Jacobs et al 2019). Both mechanisms would explain how ROP11-induced microtubule-free regions are established to spatially control cell wall deposition (Oda and Fukuda 2012a; Oda and Fukuda 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A modelling study on ROP patterning suggested that microtubule arrays, which form a barrier to ROP diffusion, cannot change the orientation of an existing pattern. This indicates that microtubules need to be oriented transversely prior to the onset of band separation (Jacobs et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Various ROPs and the aforementioned effectors are also expressed during protoxylem formation [57, 58] and striated AtROP7 patterns are observed in protoxylem [59]. Results so far indicate that the corresponding microtubule patterns are not simply a readout of a ROP pattern, as changes in microtubule dynamics affect both the dynamics and outcome of the patterning process [55, 20, 60].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies regarding how Turing-like RD processes may operate in protoxylem revealed that diffusion anisotropy, as produced by microtubule-based diffusion restriction, is critical to this system. Under such conditions, a Turing-like RD mechanism favours banded patterns whose orientation is defined by the overall orientation of the diffusion anisotropy [160]. Interestingly, this outcome is independent of whether these systems would form spot, stripe or gap patterns in absence of the diffusion anisotropy.…”
Section: Patterning Framework For Proto- and Metaxylemmentioning
confidence: 99%
“…For instance, Jacobs et al . [160] used partial differential equation models to study active ROP diffusion restriction as a mechanism of ROP pattern orientation in protoxylem development.…”
Section: Conclusion and Perspectivementioning
confidence: 99%